Glycopeptidomics Analysis of a Cell Line Model Revealing Pathogenesis and Potential Marker Molecules for the Early Diagnosis of Gastric MALT Lymphoma - Xiao, Di; Zou, Qinghua; Meng, Le; Xu, Yanli; Zhang, Huifang; Meng, Fanliang; He, Lihua; Zhang, Jianzhong (Frontiers in Cellular and Infection Microbiology, 2021)
BACKGROUND & AIMS: Gastric mucosa-associated lymphoma (GML) is a mature B cell tumor related to Helicobacter pylori (H.pylori) infection. The clinical manifestations of GML are not specific, so GML commonly escapes diagnosis or is misdiagnosed, leading to excessive treatment. The pathogenesis of H.pylori-induced GML is not well understood and there are no molecular markers for early GML diagnosis. METHODS: Glycopeptidomics analyses of host cell lines (a BCG823 cell line, C823) and C823 cells infected by H. pylori isolated from patients with GML (GMALT823), gastritis (GAT823), gastric ulcer (GAU823) and gastric cancer (GAC823) were carried out to clarify the host reaction mechanism against GML and identify potential molecular criteria for the early diagnosis of GML. RESULTS: Thirty-three samples were analyzed and approximately 2000 proteins, 200 glycoproteins and 500 glycopeptides were detected in each sample. O-glycans were the dominant glycoforms in GMALT823 cells only. Four specific glycoforms in GMALT823 cells and 2 specific glycoforms in C823 and GMALT823 cells were identified. Eight specific glycopeptides from 7 glycoproteins were found in GMALT823 cells; of these glycopeptides, 6 and 3 specific glycopeptides had high affinity for T cell epitopes and have conformational B cell epitopes, respectively. CONCLUSION: The relationship between the predominant glycoforms of host cells and the development of host disease was determined, and the glycoproteins, glycosylation sites and glycoforms might be closely related to the formation of GML, which provides new insight into the pathogenic mechanisms of H. pylori infection and suggests molecular indicators for the early diagnosis of GML.